Letter - Felixstowe & Walton Trades & Labour Council, 11 May 1926 (page 1) (Felixstowe)
1926-05-11 "Letter - Felixstowe & Walton Trades & Labour Council, 11 May 1926 (page 1)" [g0351001.jpg], 11 May 1926, Felixstowe & Walton Trades & Labour Council Local Organisation